Preparation of a mimetic and degradable poly(ethylene glycol) by a non-eutectic mixture of organocatalysts (NEMO) via a one-pot two-step process - Moins, S.; Loyer, P.; Odent, J.; Coulembier, O. (RSC advances, 2019)
A one-pot, two-step method for the preparation of degradable PEG is here presented. The full process addresses the requirements imposed by green chemistry and involves the use of a single and nontoxic non-eutectic mixture of organocatalysts. The strategy relies on the polycondensation of PEG800 after its functionalization by bio-derived 5-membered γ-butyrolactone.